Development of Domino-Based Learning Media to Improve Social Skills of Grade VII Students at SMP IT Al-Hijrah - Silpia Mahdalena Rambe; Yenti Arsini (Journal of Society Counseling, 2026)
This study aims to develop domino media as a tool in group guidance services to provide an understanding of social skills among students at SMP IT Al-Hijrah. Problems related to students’ social skills are still frequently found, such as a lack of cooperation, low empathy toward peers, and difficulties in expressing opinions. Therefore, attractive and interactive media are needed to help students understand social skills more optimally. This study employed the Research and Development (R&D) method using the 4D development model (Define, Design, Develop, Disseminate). The subjects of this study were students of SMP IT Al-Hijrah. The results of the study indicate that the domino media has a high level of feasibility, with material expert validation reaching 85% (feasible category) and media expert validation reaching 85.8% (very feasible category). A trial involving 20 students showed that the domino media was able to support students’ understanding of social skills, as indicated by better participation, improved communication skills, enhanced cooperation, and a deeper understanding of social skills. Student and teacher responses reached 90% (very good category). Thus, the domino media is considered feasible and provides optimal outcomes in guidance and counseling services to support students’ understanding of social skills.